Social leadership and contributions to rural sustainable development: a case study in Caririaçu ”“ state of Ceará (Brazil) (Sustainability in Debate, 2016)
This article aims to discuss the social leadership and sustainable rural development based on the experience of a peasant family residing in the municipality of Caririaçu, state of Ceará (Brazil). The research subject, Dona Zefinha, leader of the community Sítio São Paulo, in Caririaçu, emphasized the importance of agro-ecological experiences and its role as a driver for local development. We chose an approach based on qualitative description, conducted through literature search, non-structured interviews and participatory observation. The data were analyzed on the basis of their contents. From the perspective of sustainable rural development, Dona Zefinha's proposal is directly connected with the dimensions of sustainability, through her economic activities, the conservation of natural resources and popular education practices. Thus, it is possible to conclude that social leadership can and should be the means for the advancement of rural communities, especially those that resist the adversities of the semi-arid climate of the Brazilian Northeast region.